Monitoring Adalimumab concentration, Adalimumab antibodies, fecal calprotectin, and QuantiFERON test positivity in patients with inflammatory bowel disease - Goran Bokan; Tanja Glamočanin; Lana Mandić; Zoran Mavija (Биомедицинска истраживања, 2023)
Introduction: Inflammatory bowel diseases (IBD) are a serious global health problem affecting mostly younger and middle-aged persons. Despite the availability of variety of treatment approaches, the disease often progresses unpredictably. Biological drugs offer hope for IBD treatment. Our research share our preliminary findings regarding the monitoring of adalimumab (ADM) and adalimumab antibodies (ADA) concentrations, fecal calprotectin levels, and the frequency of QuantiFERON test positivity in IBD patients treated with biological drugs. Methods: The study was designed as a retrospective, descriptive, single-center study and was conducted at the University Clinical Center of the Republic of Srpska, Banja Luka, from January 2018 to June 2022. Medical records of patients treated at the Internal Medicine Clinic were analyzed. Patients were categorized based on underlying disease and duration of biological therapy. ADM and ADA concentrations were monitored at intervals, and QuantiFERON test positivity and fecal calprotectin levels were recorded. Statistical methods, including analysis of Variance (ANOVA) and paired t-test were performed using the SPSS program version 29. Results: Medical records of 117 patients were analyzed. Most of them, 44 were treated with adalimumab. Male patients were predominant (59.10%) in our study over females. Patients were also categorized based on the length of biological therapy. ADM and ADA concentrations increased with time (after 6, 12, 18 and 24 months), but without statistical significance. Fecal calprotectin levels decreased after 12 and 24 months of treatment. Out of the total number of patients, 53.83% of QuantiFERON positive patients were treated with adalimumab. Prophylactic isoniazid therapy was carried out in 63.6% of patients. Conclusion: Our initial experience in monitoring biological drug concentrations and fecal calprotectin levels in IBD patients showed a decrease in fecal calprotectin levels and an increase in ADM and ADA concentrations over time but there were no statistically significant differences.
Keywords: Inflammatory bowel disease (IBD); biological therapy; adalimumab concentration (ADM); adalimumab antibodies (ADA); QuantiFERON test